Seismic Performance Research on a Graded-Yielding Metal Brace with Self-Centering Functions - Zhonghai An; Wenming Wang; Hui Wang; Zhe Li; Debin Wang; Guangcai Xie (Buildings)
With the aim of achieving a graded-protection braced frame structure and minimizing the excessive residual deformation of traditional metal dampers under intense seismic action, a graded-yield-type metal self-centering brace (SC-GYMB) is proposed. The brace is composed of X-shaped and U-shaped steel plates with different yield point displacements, which jointly dissipate energy. Additionally, it employs a composite disc spring as a self-centering element to provide restoring force for the brace. The brace’s basic structure and working mechanism are described, and the theoretical model for its restoring force is derived. The ABAQUS finite element software (ABAQUS 2021) is utilized to investigate the hysteretic performance of the SC-GYMB under low-cycle reciprocating load, while thoroughly discussing the influence of various model parameters on its key mechanical behavior. The results demonstrate a strong agreement between the theoretical restoring force model and the numerical simulation results. The hysteretic curves of the braces exhibit a distinct “flag” characteristic, indicating excellent energy dissipation capacity and self-centering performance. Moreover, these curves display a hierarchical yield behavior that satisfies the seismic performance requirements for different intensity earthquakes. The deformation mechanism of X-shaped steel sheets transitions from bending deformation during the initial loading stage to tensile deformation in the subsequent loading stage. Increasing the initial pre-compression force of the combined disc spring enhances the restoration performance of the brace. Augmenting the thickness of X-shaped or U-shaped steel sheets modifies the displacement and load at both the first and second yield points, thereby enhancing energy dissipation capacity and bearing capacity of the brace; however, it also leads to increased residual deformation.